The comparison of body composition index, explosive power, and sprint speed of male student athletes after eight weeks of plyometric and weight training - Karwan Faiaq Habib; Aso Ali Mohammed; Hiwa Ahmed Rahim; Dara Latif Saifalddin; Saiwan Sirwan Mohamed; Bahroz Osman Aref; Naser Rostamzadeh; Martin Hofmeister; Do-Youn Lee (CV. FOUNDAE, 2026)
Background: Plyometric and weight training are prevalent strategies for enhancing body composition, explosive strength, and running speed, all of which are crucial for physical performance and health. Nonetheless, their comparative efficacy remains contested, particularly among non-athletic groups. Aims: This study investigated and compared the effects of an 8-week plyometric and weight-training program on body composition index (BMI), explosive performance, and running speed among twenty-eight male student-athletes. Methods: The design was selected to determine causality and directly compare the effectiveness of two different training modalities under controlled conditions. To improve scientific rigor, the randomization process, assessor blinding, and meticulous control of training parameters. Result: Both training methods yielded substantial improvements across all evaluated variables. Plyometric training resulted in significant enhancements in horizontal explosive performance, evidenced by standing long jump results (p = 0.026), as well as moderate improvements in sprint speed. Conversely, weight training produced more significant enhancements in vertical jump performance (p = 0.038) and power output (p = 0.012). Both groups exhibited substantial decreases in body mass index and body fat percentage (p < 0.001). Conclusion: These data indicate that both plyometric and weight training significantly improve physical fitness. Plyometric training primarily enhances horizontal explosive power and sprint performance, whereas weight training is more effective for improving vertical power-related outcomes.